FAILBACK FAULT ANALYSIS ON BSG 9 TYPE ELECTRIC WESEL AT PURWOKERTO STATION - Dezan Claudio; Randi Adzin Murdiantoro (Journal of Electronic and Electrical Power Applications, 2022)
Wesel (point machine) for the external equipment in the railway system that is used to move the line from a straight back position or vice versa. In the use of electric Wesel lines, there is a driving motor called a point machine. In addition, wesel also require periodic maintenance, self-laser treatment using a period of 2 weeks. Used is descriptive quantitative by presenting data on the evaluation of electric point of view in the field without any engineering or other treatment to obtain data. There is data on the percentage of the physical condition of note 53 with a yield percentage of 87.0% and a failure percentage of 8.7%. And the cumulative percentage of success is 95.7% and the cumulative percentage of failure is 8.7%. In table 5.5 there is data on the percentage of the physical condition of point 23 with a yield percentage of 87.0% and a failure percentage of 8.7%. And the cumulative percentage of success is 95.7% and the cumulative percentage of failure is 8.7%.